Dual drug load and release behavior on ion-exchange fiber: influencing factors and prediction method for precise control of the loading amount. (September 2015) - Yuan, Jing; Gao, Yanan; Liu, Tiaotiao; Wang, Xinyu; Liu, Hongzhuo; Li, Sanming
Abstract Ion-exchange fiber undergoes a stoichiometric exchange reaction and has large exchange capability, which makes it a promising candidate as a multiple drug carrier. Because combinatorial effects can act synergistically, additively or antagonistically depending on the ratio of the agents being combined, the objective of this study was to learn the dual drug loading of ion-exchange fiber and develop a mathematical method for precisely control of the loading amount. Atenolol and Gatifloxacin, with different loading behaviors into strong cationic ion-exchange fiber ZB-1, were used to build a representative of dual loading. Not suitable pH value of drug solutions could make simultaneous loading fail, while the change of drug solution volume hardly affected the equilibrium. Ion-exchange groups occupied by the drug which owned lower affinity to fiber could be grabbed by the higher affinity drug, indicating the existence of competition between drugs. Thermodynamic model was introduced to guide the loading prediction and a favorable relevance had been shown between determined and predicted data. The release behaviors of each drug from dual drug–fiber complex were similar to those from single drug–fiber complexes.